Tatalaksana Terapi Radiasi Pada Pasien Cito Bleeding Kanker Serviks Di Instalasi Radioterapi RSUD Provinsi NTB - Yusril Alvarezy Majid; Putu Irma Wulandari; Cory Amelia (Pusat Riset dan Inovasi Nasional, 2023)
Background: Treatment of radiation therapy in patients with cervical cancer citobleeding at the Radiotherapy Installation of the NTB Provincial Hospital uses a 2D technique with 2 radiation fields, namely AP (Antero Posterior) and PA (Postero Anterior). The aim of this study is to describe the management of radiation therapy in patients with cervical cancer bleeding in the radiotherapy installation of the NTB Provincial Regional Hospital and its advantages and disadvantages. Method: This type of research is qualitative descriptive research with a case study approach. The author conducted interviews with research subjects, namely 1 radiation oncologist, 1 medical physicist and 3 radiographers/RTT. The author took the collected data such as images and medical record data. Data was collected using interview transcripts, then processed using a categorization table and an open coding system. Results: Based on the results of the author's observations and interviews, the management of radiation therapy in Cito bleeding cervical cancer patients at the Radiotherapy Installation of the NTB Provincial Regional Hospital uses a 2D technique with a dose of 3 x 3 Gy per fraction. The advantage of radiation therapy management for patients with bleeding cervical cancer is the use of a 2D technique which is simpler and faster so that the patient can be immediately irradiated, but the disadvantage is that it produces less than optimal dose distribution to the target and organs at risk (OAR). Conclusion: Treatment of radiation therapy in patients with bleeding cervical cancer at the NTB Provincial Hospital Radiotherapy Installation uses a 2D two-field AP and PA technique with a dose of 3 x 3 Gy per fraction to stop bleeding. The advantage of using the 2D technique is that it is faster and simpler, while the disadvantage is that the dose distribution is not optimal.